Gallic acid and methyl gallate enhance antiproliferative effect of cisplatin on cervical cancer (HeLa) cells - Norlida Mamat,; Hasmah Abdullah,; Hermizi Hapidin,; Noor Fatmawati Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cervical cancer is the fourth most common cancer-related death affecting women. The drug resistance, toxicities and undesired side effects become the major limitation in cisplatin-based chemotherapy. Gallic acid and methyl gallate are the most abundance phenolic compounds that are widely distributed in plants. This study was conducted to evaluate the antioxidant and antiproliferative activity of gallic acid and methyl gallate and their synergistic effects in combination with cisplatin towards cervical cancer (HeLa) cells. The antioxidant activity of gallic acid and methyl gallate was measured by using 1, 1-diphenyl-2-picrylhydrazyl radical (DPPH) scavenging assay. Antiproliferative activity of gallic acid, methyl gallate and cisplatin on HeLa and NIH/ 3T3 cells was determined using MTT assay. The effect of gallic acid and methyl gallate combined with cisplatin were then determined by CompuSyn software. Gallic acid and methyl gallate showed strong antioxidant activity with EC50 value of 18.23 µM and 19.39 µM, respectively. The IC50 of gallic acid, methyl gallate and cisplatin on HeLa cells were 13.44 µg/mL, 16.55 µg/mL, and 8.04 µg/mL whereas in NIH/3T3 cells were 32.90 µg/mL, 35.70 µg/mL, and 6.57 µg/mL. Cisplatin combined with fixed concentration of gallic acid and methyl gallate could inhibit the proliferation of HeLa cells greater than cisplatin alone. Interestingly, gallic acid and methyl gallate in combination with cisplatin at the concentration of 0.51-4.02 µg/mL have shown synergistic effects. Therefore, our study suggested that gallic acid and methyl gallate in combination with cisplatin have the potential to be developed as chemotherapeutic agents for cervical cancer.